Screening of non-alcoholic steatohepatitis (NASH)-related datasets and identification of NASH-related genes - Liu, Ming-Jiang (Int J Clin Exp Pathol, 2021)
Non-alcoholic steatohepatitis (NASH) is a common liver disease in the western world. The mechanisms behind NASH formation are poorly understood, but there may be multiple targets considering the disease’s multifactorial nature. To explore the genes related to the pathogenesis of NASH, we downloaded clinical data and gene expression of NASH patients from the Gene Expression Omnibus database (GEO). We identified 281 genes with a common expression in two NASH-related datasets (GSE89632 and GSE83452), suggesting that they may be related to NASH. Further study showed that Angptl4, Foxo1, and Ttc39B might be essential for NASH progression, and these have been poorly studied. Therefore, we explored their roles in NASH. Our data show that these genes participate in the development of NASH through lipid metabolism. This suggests that the three genes can be used as therapeutic targets in NASH.